Usefulness of marker‐assisted selection to improve maize for increased resistance to Sesamia nonagrioides attack with no detrimental effect on yield. (29th January 2019) - Samayoa, Luis F.; Butrón, Ana; Malvar, Rosa A.
Abstract : Two decades of investigations on maize resistance to Mediterranean corn borer ( Sesamia nonagrioides Lefebvre; MCB) have shown that breeding for increased resistance to stem tunnelling by MCB often resulted in reduced yield because significant genetic correlation between both traits exists in some backgrounds. Unlike phenotypic selection, marker‐assisted selection (MAS) could differentiate markers linked only to one trait from those linked simultaneously to yield potential and susceptibility to the pest. In the current study, the suitability of MAS for improving resistance to stem tunnelling without adverse effects on yield has been tested. The unfavourable genetic relationship between yield potential and susceptibility could be overcome using MAS. Gains obtained using MAS were weak, because genetic variance explained by the quantitative trait loci (QTL) was low but results encourage us to persevere in using marker information for simultaneous improvement of resistance and yield especially if genome‐wide approaches are applied. Approaches to detect QTL are widely used, but studies on the suitability of markers linked to QTL for performing MAS have been mostly neglected. Abstract : The unfavorable genetic relationship between yield potential and susceptibility could be overcome using MAS. Gains obtained using MAS were weak because genetic variance explained by the quantitative trait loci (QTL) was low but results encourage us to persevere in using maker information for simultaneous improvement of resistance and yield especially if genome‐wide approaches are applied.